Degradation kinetics of α‐conotoxin TxID. Issue 9 (2nd August 2019) - Xu, Pan; Xiong, Yang; Liu, Yiqiao; Yu, Shurun; Zhangsun, Dongting; Wu, Yong; Luo, Sulan
Abstract : α‐Conotoxin TxID is a potent α3β4 nicotinic acetylcholine receptor (nAChR) antagonist. The stability and forced degradation of TxID under different stress conditions were analyzed. The major degradation products of TxID were analyzed using liquid chromatography–tandem mass spectrometry. The activities of degradation products were determined by electrophysiological assays. The results indicate the stability and activity of TxID under various chemical and physical conditions. Abstract : α‐Conotoxin (CTx) TxID is a potent α3β4 nicotinic acetylcholine receptor (nAChR) antagonist that has been suggested as a potential drug candidate to treat addiction and small cell lung cancer. The function and structure of TxID have been well‐studied, but analyses of its stability have not previously been reported. The purpose of this study was to analyze the stability and forced degradation of TxID under various conditions: acid, alkali, water hydrolysis, oxidation, light, thiols, temperature, ionic strength and buffer pH. Different degradation products were formed under various conditions, and the degradation patterns of TxID showed pseudo‐first‐order kinetics. TxID degraded slowest at pH 3 within a pH range of 2–8. The major degradation products were analyzed using liquid chromatography–tandem mass spectrometry and the activity of the main product with α3β4 nAChR was analyzed using electrophysiological methods. Our analysis of TxID stability may aid the selection of appropriate conditions for peptide production, packaging and storage.